Prevalence of thyroid dysfunction in East and West Coast of Malaysia - Shahar, Mohammad Arif; Saud Gany, Siti Liyana; Omar, Ahmad Marzuki; Abdul Wahab, Norasyikin; Sukor, Norlela; Kamaruddin, Nor Azmi (Malaysian Endocrine & Metabolic Society, 2016)
Objectives. To determine the prevalence of thyroid dysfunction in the coastal communities of Malaysia. This study is part of a nationwide study looking into the prevalence of thyroid disorders.